2008
DOI: 10.1111/j.1528-1167.2008.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic birth defects after prenatal exposure to antiepileptic drugs

Abstract: SUMMARYMaternal epilepsy has a potential for fetal injury, either antiepileptic drug (AED)-induced or as a consequence of seizures per se. The intent of this article is to explore this relationship, discussing similar patterns of malformations seen with AEDs or different disease exposure during pregnancy, and the potential role of gap junctional intercellular communication in abnormal morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 105 publications
(128 reference statements)
0
1
0
3
Order By: Relevance
“…Mothers of cases that gave history of taking different types of unprescribed medications were more than mothers of controls. Different studies showed an association between different types of drugs and CAs such as Uziel and Rozental [32] who showed that antiepileptic drug (AED) administration resulted in CNS anomalies and Etemad et al [33] who found a high frequency of major anomalies, heart defects, and hypoplasia of the midface and fingers, known as anticonvulsant embryopathy, in infants exposed to anticonvulsant drugs in utero mainly AEDs. Yakoob et al, meta-analysis, suggested an increased risk of CVS anomalies, orofacial clefts, and NTDs following intake of oral beta-blockers in the first trimester of pregnancy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of cases that gave history of taking different types of unprescribed medications were more than mothers of controls. Different studies showed an association between different types of drugs and CAs such as Uziel and Rozental [32] who showed that antiepileptic drug (AED) administration resulted in CNS anomalies and Etemad et al [33] who found a high frequency of major anomalies, heart defects, and hypoplasia of the midface and fingers, known as anticonvulsant embryopathy, in infants exposed to anticonvulsant drugs in utero mainly AEDs. Yakoob et al, meta-analysis, suggested an increased risk of CVS anomalies, orofacial clefts, and NTDs following intake of oral beta-blockers in the first trimester of pregnancy [34].…”
Section: Discussionmentioning
confidence: 99%
“…En sık görülen konjenital malformasyonlar; kardiyovasküler ve ürogenital sistem anomalileri, orofasiyal defektler, nöral tüp defekti, iskelet anormallikleri, dismorfik özellikler, davranış bozukluğu ve IQ düşüklüğüdür. [5][6][7] Gebelikte kullanılan antiepileptik ilaçların, çocukta EEG anomalisi gelişiminde rol aldığını bildiren çalışmalar da mevcuttur. [8] Epilepsi ve gebelik konusu dört ana başlık altında incelenecektir: I-Gebeliğin seyri ve doğum: İntrapartum ve postpartum hemoraji, hipertansiyon gibi gebelik komplikasyonları ile prematüre doğum, fetal ve neonatal ölüm oranları epilepsili gebelerde daha sıktır.…”
Section: Introductionunclassified
“…[12,19,20] IV-Konjenital malformasyonlar ve kognitif yan etkileri: Antiepileptik ilaçların teratojen yan etkilerine dikkat çeken pek çok çalışmada malformasyon oranı %4-9 olarak bildirilmiştir. [5,9,10,[13][14][15][16] Bizim çalışmamızda bu oran %6.8 olarak tespit edilmişti ve özellikle diş ve dismorfik özelliklerin valproat alanların çocuklarında daha sık görüldüğü bildirilmiştir. [21] Antiepileptik ilaçların özellikle de valproatın düşük IQ ve otistik spektrum hastalıklarına neden olduğu, karbamazepin, lamotrijin, levetirasetam ve fenitoinin kognitif gelişime etkisinin olmadığı yönünde bildiriler mevcuttur.…”
Section: Introductionunclassified
“…είναι η ηλικία των γονέων, μητέρας63 και πατέρα64 , η σειρά γέννηση65 και ο πιθανώς συνωστισμός μέσα στη μήτρα λόγω πολύδυμων κυήσεων66 . Ανασταλτική επίδραση στην εμβρυϊκή ανάπτυξη ασκούν επίσης, χρόνια νοσήματα της μητέρας, λήψη φαρμάκων (κυρίως τα αντιυπερτασικά67 και αντιεπιληπτικά68,69 ) ή αλκοόλ, ο υποσιτισμός, το αλκοόλ, η χρήση ναρκωτικών και το κάπνισμα.Είναι γνωστό ότι απόγονοι μητέρων με σακχαρώδη διαβήτη τύπου Ι διατρέχουν μεγαλύτερο κίνδυνο εμφάνισης συγγενών δυσπλασιών. Η συχνότητα των ανωμαλιών σχετίζεται με το σχετικά πλημμελή έλεγχο των επιπέδων του σακχάρου στο αίμα, ιδιαίτερα κατά το πρώτο τρίμηνο της κύησης70 .…”
unclassified